purification asparaginase produced from Bacillus licheniformis (Damascus University Journal of agriculture sciences, 2022)
Asparaginase produced by Bacillus licheniformis using submerged fermentation under optimized conditions was purified. The purification process included the following steps; precipitation of protein by 80% acetone followed by sephadex G-100 gel filtration column then separation on  DEAE- Sepharose column chromatography .Folds of purification of asparaginase reached 283.86 fold with specific activity of 667.08 IU/ml.
Keywords: asparaginase; purification; Bacillus licheniformis; submerged fermentation